An assessment of records management practice in selected local government councils in Ogun State, Nigeria (2016)
What government does/fails to do is conveyed to the public largely by records and information of various types in the public service, without which there will be no government. When records are poorly managed, much time is involved in sorting and locating needed information from large volumes of records. The rate of records misplaced or lost from which useful information for decision making is usually obtained makes it difficult to provide concise and up-to-date records of both past and present operations, raising the challenge of effective record-keeping. Thus this study examined records management practices in selected local government councils in Ogun State, Nigeria, adopting the descriptive survey research method using questionnaires for data collection. Its population comprised 415 records of personnel in the selected councils, of which 208 were sampled using simple random technique. From the 208 copies of the questionnaire administered on the registry personnel, 150 copies were useable, with a 72.12% response rate. Descriptive statistics were used for the analysis. The results indicated a prevalence of paper as the dominant medium for recording/conveying information in the councils with most of these being either in active state, semi-active, and vital and were kept and maintained in the registry, while in-active records were kept in the records store. Storage facilities for record-keeping were insufficient. Security measures against unauthorized access to records were by restrictions and subject users to managerial clearance. The study concluded that council records were in chaos and recommended the formulation of coherent records management policy, adequate budgetary provision, and adequate finance.